Language ideologies in transnational families with Israeli background in Finland - Bloch, Gali (Frontiers in Sociology, 2024)
Transnational families manage complex language dynamics, with multifaceted linguistic practices representing a key aspect in shaping communication among family members, where balancing heritage and host country languages impacts both cultural preservation and integration into a new society. The situation complicates when multilingual and multicultural families relocate to a country with a new majority language, while maintaining ties to their original society. This study analyzes language ideologies of seven transnational participants who were repatriated to Israel from post-Soviet states (PSS) during childhood and decades later relocated to Finland with their children. The study based on the data gathered through semi-structured interviews addresses two key questions: What are the language ideologies held by Israeli Generation 1.5 parents in transnational multilingual families residing in Finland? What are the parental language beliefs concerning their and their children's social integration in Finland? Thematic data analysis reveals parents' efforts to balance multiple languages, driven by their overwhelmingly positive views on their children's multilingualism. The language choices impact language acquisition and maintenance, while also preserving old social connections and building new ones for the entire family. Findings highlight key factors shaping parental ideologies on language transmission, multilingualism, code-switching, and integration, mostly influenced by personal convenience and practicality. This study presents a novel perspective on the language ideologies of multilingual parents. By examining individual parental beliefs and attitudes toward each language involved, it identifies recurring collective ideologies regarding multilingualism overall and each specific language, thus enriching discussions on linguistic diversity and multicultural integration in transnational contexts. Additionally, informing policymakers about the linguistic challenges encountered by transnational multilingual families can facilitate the promotion of inclusive educational practices and foster cultural awareness initiatives, thus contributing to the creation of a more equitable and supportive environment for such families managinglinguistic diversity.